Supplementary materials for PhD thesis “The Origin of Basaltic Lava Flow Textures” - Marie-Noëlle Guilbaud (2006)
This dataset comprises the files contained on a CD-ROM which was attached to the thesis when it was submitted in 2006 . It was uploaded to ORDO in 2024 for preservation purposes. For more information, please refer to the thesi s The Origin of Basaltic Lava Flow Textures . This study addresses the links between the surface morphologies, internal structure, and microtexture of basaltic lava flows. The AD 1783-84 Laki eruption in south Iceland produced a 600 km2 basaltic lava flow-field dominated by rubbly pāhoehoe surface morphology. Field observations and aerial photograph interpretation show that the lava surface gradually changed from spiny to slabby and then to rubbly along single flows through repetitive crust disruption at the active front. The rubble was compressed into ridges when lava advance was obstructed and during large lava surges that coincided with the opening of new eruptive fissures. Fluid lava was transported in an extensive network of tubes that formed within the flows.Petrological study of Laki near-vent tephra and lava surface samples shows that, during the eruption, the magma lost ~ 1 wt. % of water during ascent, which induced melt undercooling and triggered groundmass crystallization. This caused an ~ 10% anorthite gap across plagioclase phenocrysts and drove considerable microlite formation (up to 30 vol.%) in the early stages of flow. It is estimated that fluid lava was transported from the vent to the most distal active front, 60 km from the vent, with cooling rates of < 0.5°C/km. Young lava flow-fields in the Reykjanes Peninsula (Iceland), and some flows from the flood basalts of the Columbia River Province (USA), have surface and internal structures intermediate between rubbly pāhoehoe and 'a'ā. The increasing size and decreasing number density of plagioclase microlites with increasing depth in these flows, as in the Laki lavas, indicate that solidification rates decreased sharply inwards. Differences between sections are attributed to variations in lava bulk composition and the ...